Karakterisasi Selulosa Bakteri Hasil Fermentasi Limbah Air Kelapa dan Pemanfaatannya Sebagai Penyangga Pembentukan Perak Nanopartikel - Mutiara, Tintin; Wardatur Rohmah, Isnaeni; Okta Berinda, Aulia (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Bacterial cellulose (BC) is a biopolymer resulting from sugar fermentation by exopolysaccharide-producing bacteria. BC production can be done using various agricultural and industrial wastes as raw materials. This makes BC one of the leading choices for green technology. BC produced from coconut water fermentation is known as nata de coco. Nata de coco has several superior properties, including high purity, crystallinity, chemical stability, heat resistance, good water retention capacity, mechanical properties, and biocompatibility. The unique properties of BC allow its application as a support and stabilizer for silver nanoparticles in composite form. The synthesis of silver nanoparticle composites in bacterial cellulose can be done using an environmentally friendly method. In this study, BC was produced from the fermentation of coconut water waste by Acetobacter xylinum bacteria. The characteristics of the resulting BC were studied, including thickness, Water Retention Capacity (WRC), cellulose content, yield, and swelling properties. In addition, the resulting BC is utilized as a support and stabilizer for forming silver nanoparticles. The presence of silver nanoparticles in the BC structure was analyzed using a Scanning Electron Microscope (SEM) and Energy-Dispersive X-ray (EDX). The analysis results showed that the silver content was 22.20% in the BC structure with a fermentation time of 3 days, and 15.52% in BC with a fermentation time of 5 days.